Lymph node retrieval in colorectal cancer: determining factors and prognostic significance - Betge, Johannes; Ebert, Matthias (International journal of colorectal disease, 2017)
Purpose: The study aimed to analyze clinicopathological factors that determine the extent of lymph node retrieval and to evaluate its prognostic impact in patients with colorectal cancer (CRC). Methods: The number of retrieved lymph nodes was analyzed in 381 CRC specimens. Lymph node count was related to different clinicopathological variables by binary logistic regression. Progression-free survival (PFS) and cancer-specific survival (CSS) were determined using the Kaplan-Meier method and Cox regression models. Results: The median number of retrieved lymph nodes was 20 (mean 21 ± 10, range 1-65) in right-sided, 13 (16 ± 10, 1-66) in left-sided, and 15 (18 ± 11, 3-64) in rectal tumors. The number of retrieved lymph nodes was independently associated with T-classification (p < 0.001), N-classification (p = 0.014), and tumor size (p = 0.005) as well as right-sided tumor location (p = 0.012). There was no association with age, sex, tumor grade, mismatch-repair status, and lymph or blood vessel invasion. The longer the surgical specimen, the higher were the numbers of retrieved and positive lymph nodes (p < 0.001, respectively). In patients with locally advanced (T3/T4) tumors (n = 283), analysis of more than 12 lymph nodes was independently associated with PFS (HR = 0.63, p = 0.025) and CSS (HR = 0.54, p = 0.004). In the subset of T3/T4 N0 patients (n = 130), analysis of more than 12 lymph nodes similarly proved to be an independent predictor of outcome (PFS, HR = 0.48, p = 0.046; OS, HR = 0.41, p = 0.026). Conclusion: The number of retrieved lymph nodes is associated with higher tumor stage, tumor size, and right-sided location. Low lymph node count indicates adverse outcome in patients with locally advanced (T3/T4) disease.